Systematic review of feedback literacy instruments for health professions students - Mohd Noor, Mohamad Nabil; Fatima, Sahar; Grace Cockburn, Jessica; Romli, Muhammad Hibatullah; Pallath, Vinod; Hong, Wei-Han; Vadivelu, Jamuna; Foong, Chan Chong (Elsevier Ltd, 2024)
Successfully managing and utilizing feedback is a critical skill for self-improvement. Properly identifying feedback literacy level is crucial to facilitate teachers and learners especially in clinical learning to plan for better learning experience. The present review aimed to gather and examine the existing definitions and metrics used to assess feedback literacy (or parts of its concepts) for health professions education. A systematic search was conducted on six databases, together with a manual search in January 2023. Quality of the included studies were appraised using the COSMIN Checklist. Information on the psychometric properties and clinical utility of the accepted instruments were extracted. A total 2226 records of studies were identified, and 11 articles included in the final analysis extracting 13 instruments. These instruments can be administered easily, and most are readily accessible. However, ‘appreciating feedback’ was overrepresented compared to the other three features of feedback literacy and none of the instruments had sufficient quality across all COSMIN validity rating sections. Further research studies should focus on developing and refining feedback literacy instruments that can be adapted to many contexts within health professions education. Future research should apply a rigorous methodology to produce a valid and reliable student feedback literacy instrument.